Modern trends a request for international legal assistance in criminal proceedings to the General prosecutor of Ukraine - Стринатко, Юрій Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article outlines the legal framework and analyzes the dynamics of appeals to the competent authoritiesof the Prosecutor General of Ukraine with requests for international legal assistance in criminal proceedings.